Rhetoric-poetic-hermaneutic - Ricoeur, Paul; Martínez, Edgar Mauricio (Estudios de Filosofía, 1991)
The study that follows grew out of a lecture given in 1970 at the Belgian Institute for Higher Studies in the presence and under the chairmanship of Professor Perelman. Since this conference has not been public, I receive as an honor the invitation to associate myself today with the tribute paid by his friends and his disciples to the master philosopher in Brussels for several decades.